Effect of different training stress on leptin, cortisol and testosterone in elite female rowers - Ding, Y.; Guo, X.; Lu, H.; Zeng, F. (Journal of Exercise Science & Fitness, 2004)
The purpose of this study was to compare the influence of different training stress on fasting concentrations of plasma leptin, cortisol and testosterone in elite female rowers. Seven national female rowers underwent a 3-week period of heavy training and a 1-week tapering training. The stress hormones were measured before (PT) and after (HT) the heavy training period and after the following tapering period (TP). Leptin concentrations were measured in duplicate by radioimmunoassay. Mean training time of HT and TP were 22.0 hrs.week-1 and 8.2 hrs.week-1, respectively. The 3-week heavy training induced a significant reduction (P <0.05) in the fasting leptin concentrations from 7.73 +2.63 to 4.32 +1.28 ng.ml-1. Fasting plasma leptin was significantly increased by the end of the 1-week tapering period (10.69 +4.31 ng.ml-1). Meanwhile, resting cortisol of PT did not significantly alter in HT in spite of a significant increase in TP. No significant change in testosterone was found throughout the training and tapering periods (P >0.05). These findings suggested that the fasting concentration of plasma leptin may be more sensitive to the rapid and pronounced changes in training stress by comparing with those of cortisol and testosterone and it may be a potential indicator used in monitoring relative training stress in elite female rowers.